Zhiyan’s 智儼 Theory of Suchness (Ch. Zhenru 真如) and the Dependent Arising of the One Vehicle of the Distinct Teaching: With a Focus on the Influence of the Ratnagotravibhāga (Ch. Jiujing Yisheng Baoxing Lun 究竟一乘寶性論) - Li, Zijie (Religions, 2024)
Zhiyan 智儼 (602–668) is considered the second patriarch of the Chinese Huayan 華嚴 (Jp. Kegon) school. Zhiyan gave his scholarly attention to the Dilun School 地論宗 and Shelun School 攝論宗. By his period, the reunification of the North and South had permitted the Dilun and Shelun lineages to begin to merge, and the texts on which they were based had a common origin in the Indian Yogācāra and Tathāgatagarbha. In this article, I focus on Zhiyan’s conceptual innovations and their background. My chief concerns are twofold: the first is to review several terms and teachings as representative examples of the creative practice of Zhiyan and the second is to identify his roots in the earlier traditions of Indian and Chinese Buddhism. I focus on the translation and understanding of the term zhenru 真如 (Skt. tathatā; suchness/thusness), which is a crucial expression used in descriptions of ultimate truth in Buddhism. By investigating the terms through the lens of the Ratnagotravibhāga (=RGV), I consider what tathatā, dhātu and gotra signified in their Indian usage and how these meanings evolved in the process of the appropriation of these concepts in China, especially in Zhiyan’s writings. Furthermore, through this analysis, I aim to explore Zhiyan’s attitude towards the Jiujing yisheng baoxing lun 究竟一乘寶性論 (=BXL), the Chinese translation of the RGV, and examine how he absorbed and utilized this significant treatise, which was compiled in India and translated in Northern China. We cannot find even one clear interpretation defining suchness as unconditioned dharma in the Dasheng qixin lun 大乘起信論 (=AF; Awakening of Mahāyāna Faith). In the AF, it is stated that suchness is initially pure. However, due to the fumigation of ignorance, the marks and features of defilement will appear on pure suchness. Suchness, being connected with foundation consciousness, has been regarded as the foundation or origin of conditioned arising in the She dasheng lun chao 攝大乘論抄 (T2806), a significant commentary on the She dasheng lun 攝大乘論 translated by Paramārtha 真諦 (499–569), who has been associated with the AF. Building on this trend in the interpretation of suchness, Zhiyan employs both the AF and the BXL to expound his theory of suchness. He initially utilizes the theory of suchness from the AF and the BXL to argue that all phenomena, including delusion, could arise from suchness. Zhiyan asserts the fumigation/perfume of suchness. The background of Zhiyan’s theory of suchness is based on the AF. However, while the AF only mentions the fumigation/perfume of suchness, Zhiyan adds that suchness does not inherently maintain its self-nature but arises conditionally. This marks a significant difference, or development, between the theory of suchness in the AF and that in Zhiyan’s Huayan doctrinal system. In my view, the answer lies in the BXL, which Zhiyan himself regards as a key text alongside the AF as the basis for his theory of suchness. Zhiyan finds an intimation of the precious truth in the commentaries of Huiguang 慧光, who was a disciple of Ratnamati, the translator of the BXL, and the founder of the southern branch of the Dilun School. Zhiyan finds the doctrine of infinite dependent arising according to the one vehicle of the distinct teaching (Ch. biejiao yisheng 別教一乘) in Huiguang’s commentaries. It indicates that the renderings and interpretations of Ratnamati and Huiguang seem to have deeply influenced Zhiyan. For a long time, many scholars have believed that the RGV had only a minimal impact on East Asian Buddhism, and few have pointed out its influence on Zhiyan. However, through the analysis in this article, I find that Zhiyan places significant importance on the RGV and its Chinese translation BXL.